The creature of the pines - Gidwitz, Adam; Aly, Hatem (New York, NY : Dutton Children's Books, 2018)
After encountering a Jersey Devil while on a field trip to the Pine Barrens, Elliot and his new friend Uchenna help their weird teacher Professor Fauna rescue the mythological creature from a pair of greedy billionaire brothers.
Map on end paper.
Keywords: Animals, Mythical -- Juvenile fiction; Animal rescue -- Juvenile fiction; Friendship -- Juvenile fiction; Clubs -- Juvenile fiction; Animals, Mythical -- Fiction; Animal rescue -- Fiction; Friendship -- Fiction; JUVENILE FICTION -- Legends, Myths, Fables -- General; JUVENILE FICTION -- Social Issues -- Friendship; JUVENILE FICTION -- Historical -- General; Friendship -- Fiction; Animals, Mythical -- Fiction; Animal rescue -- Fiction; Animal fiction; Fantasy fiction; Fiction; Juvenile works; Fantasy fiction; Animal fiction; Novels; Fantasy fiction